Growing old in a transnational social field: belonging, mobility and identity among Italian migrants - Zontini, Elisabetta (Taylor & Francis, 2014)
This article focuses on ageing in transnationalism. Drawing on the experiences of Italians in the UK as a paradigmatic example of settled European migrants, it explores the lived experiences of this group of older migrants. Using Levitt and Glick Schiller’s framework,it concentrates first on migrants’ways of being and then on their ways of belonging. The article argues that a transnational lens is necessary to understand the experiences of older migrants and that a focus on older people needs to be incorporated into studies of transnationalism. Through a discussion of their narratives and experiences, the article offers a long view on the migration process and brings attention to the significance of gender, time and the life course to understand both migrants’transnationalism and their integration.